Macro-Economic Variables and Stock Market Performance: Empirical Evidence from Colombo Stock Exchange - Amaresh, M.; Anandasayanan, S.; Ramesh, S. (My University, 2020)
Stock market performance is considered as a significant indicator of financial and economic circumstances of a country. In a nutshell, a secured and regulated financial environment is being provided by the stock market where shares can be transacted at lower operational risk. The stock market also functions as a platform through savings, and investments of individuals are channelized into productive investment proposals. It allows capital formation and economic growth for the nation. The ultimate objective of this study is to examine the impact of macro- economic variables on stock market performance. The macro- economic variables (independent variables) used in this research study are Inflation, Interest Rate, and GDP. Stock market performance (All-Share Price Index) is the dependent variable. 120 Monthly observations from January 2009 to December 2018 had been taken for the study. The Augmented Dickey Fuller’s unit root test, Ordinary Least Squares Regression and Correlation analysis were applied to the variables. The results of correlation analysis indicated that inflation and Stock market performance are positively associated meanwhile interest rate, and GDP and Stock market performance are negatively correlated. The Ordinary Least Square results showed that nearly 75% of the variation in all share price index is explained by the three macroeconomic variables, GDP, TB and WPI. The study suggested some of the possible reasons for the positive impact of Inflation on the Colombo Stock market performance, and negative impact of Interest Rate on Stock market performance and recommended that efforts should be made to improve the Stock market performance.
Keywords: Macro-economic variables; All-Share Price Index; Economic Growth; Colombo Stock Exchange